Rotaviruses Methods and Protocols - Gray, James.; Gray, James.; Desselberger, Ulrich.; Desselberger, Ulrich. (Methods in Molecular Medicine,, 2000)
In Rotaviruses: Methods and Protocols, James Gray and Ulrich Desselberger have assembled a comprehensive collection of established and cutting-edge methods for studying and illuminating the structure, molecular biology, pathogenesis, epidemiology, and prevention in animal models of infection with rotaviruses, an important cause of infant morbidity and mortality. Presented by experts in the fields of animal and human rotavirus infections and rotavirus vaccine research, these readily reproducible methods detail molecular and other modern techniques, and include relevant background information and various notes to ensure reproducible and robust results. Authoritative and up-to-date, Rotaviruses: Methods and Protocols offers researchers today's benchmark compendium of experimental methods for the investigation of this medically significant virus.